Effect of Graded Levels of G-probiotic on Growth, Survival and Feed Conversion of Tilapia, Oreochromis mossambicus - A.T., Ramachandra Naik; H., Shivananda Murthy; T.J., Ramesha (Fishery Technology, 2025)
The effect of G-probiotic on growth, survival and feed conversion in Oreochromis mossambicus was studied. Three diets formulated by incorporating the growth promoter, Gprobiotic at 5.0, 7.5 and 10.0 g/kg diet respectively were evaluated. The crude protein content was 30% in each diet. The diets were fed to triplicate groups of tilapia fry twice daily at a level of 10% of their biomass for 90 days. Water quality parameters recorded during the experimental period were within the range suitable for tilapia growth. The results showed better specific growth rate, food conversion rate and protein efficiency ratio in the group which was given 7.5 g G-probiotic/kg diet.